2007
DOI: 10.1007/s10803-007-0431-z
|View full text |Cite
|
Sign up to set email alerts
|

Dream Content Analysis in Persons with an Autism Spectrum Disorder

Abstract: Dream questionnaires were completed by 28 young adults with autism spectrum disorder (ASD) participants. Seventy-nine typically developed individual served as the control group. In a subset of 17 persons with ASD and 11 controls matched for verbal IQ, dream narratives were obtained following REM sleep awakenings in a sleep laboratory. Questionnaires revealed that participants with ASD, compared to controls, had fewer recollections of dreaming, fewer bad dreams and fewer emotions. In the sleep laboratory, dream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Persons with ASD are known to present a reduced verbal and nonverbal expression of emotional information. This was replicated here, as in our previous study (Daoust et al, 2007) in which we observed that participants with ASD reported fewer emotions in questionnaires and in laboratory dream reports. We also found that participants with ASD reported fewer negative emotions in their dreams than controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Persons with ASD are known to present a reduced verbal and nonverbal expression of emotional information. This was replicated here, as in our previous study (Daoust et al, 2007) in which we observed that participants with ASD reported fewer emotions in questionnaires and in laboratory dream reports. We also found that participants with ASD reported fewer negative emotions in their dreams than controls.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, dream reports of persons with ASD following REM sleep awakenings have fewer words and significantly fewer mention of content elements such as emotions, objects, social interactions, characters, and activities compared to controls. To better assess the features of dreams in ASD, we recently analyzed dream habits and narratives of a larger group of persons with ASD using questionnaires as well as laboratory REM sleep awakenings (Daoust, Lusignan, Braun, Mottron, & Godbout, 2007) Questionnaire results showed a lower recall of dreams and fewer bad dreams in participants with ASD compared to controls. Other formal dream features were similar between groups except for a lower relative frequency of emotions, which was confirmed in laboratory dream reports following awakenings in REM sleep.…”
mentioning
confidence: 99%
“…One functional meaning of the present results relates to mental activity during REM sleep, i.e., dreaming. Based on questionnaires, we have previously shown that recall of dream content for the past month was lower in ASD adults compared to controls ( 37 ),while others have reported that dream recall was associated with increased beta EEG activity over occipital recording sites ( 38 ). This is consonant with the fact that, in the present study, beta EEG activity over occipital recording sites was found to be lower in the ASD group.…”
Section: Discussionmentioning
confidence: 99%
“…To begin with, children with autism have difficulties with emotion self-regulation, comprehension, compliance with the parental instructions and with expressing their apprehensions [ 22 , 23 ]. Children with ASD have fewer recollections of dreams and distinctive slower alpha EEG patterns and asymmetries [ 24 , 25 ].…”
Section: Autism Spectrum and Neurodevelopmental Disordersmentioning
confidence: 99%